Nilai-Nilai Islam dalam Tradisi Pernikahan Masyarakat Etnis Melayu di Tanjung Balai - Lubis, Siti Nurhaliza; Siregar, Yusra Dewi; Yasmin, Nabila (Warisan: Journal of History and Cultural Heritage, 2023)
Marriage customs serve as a tangible manifestation of the confluence of Islamic values and local culture, combining into a unified sacred process. This study explores the wedding traditions of the Malay ethnic group in Tanjung Balai, including their historical roots, customary rituals, and their correlation with Islamic values. The research aims to provide a comprehensive description of the marriage culture commonly practiced by the people of Tanjung Balai, while also expanding scholarly insights into the integration of Islam and Indonesian culture. Remarkably, these traditions have endured for a significant duration and have ties to the spread of Islam from the Sultanate of Aceh. This qualitative research, utilizing anthropological and historical research methods, involves four phases: heuristics (source collection), source criticism, interpretation, and historiography. The study concludes that Islamic values incorporated into the wedding traditions of the Malay ethnic group in Tanjung Balai have influenced the orientation of local cultural values towards an Islamic context. Furthermore, the evolution of this culture over time represents a gradual adaptation to changing societal dynamics, drawing inspiration from the local indigenous community.